United Kingdom : Financial System Stability Assessment including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Insurance Supervision, Securities Regulation, Payment Systems, Monetary and Financial Transparency, Securities Settlement Systems, and Anti-Money Laundering and Countering Terrorist Financing. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper presents key findings of the Financial System Stability Assessment for the United Kingdom, including Reports on the Observance of Standards and Codes on Banking Supervision, Insurance Supervision, Securities Regulation, Payments Systems, Monetary and Financial Policy Transparency, and Securities Settlement Systems. The financial sector of the United Kingdom is supported by a financial policy framework that has been significantly strengthened in a number of ways in recent years, and that in many respects is at the forefront internationally. The supervision framework complies or largely complies with most international standards and codes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet